Salinisation source(s) and mechanism(s) in shallow alluvial aquifers along the Buffels River, Northern Cape Province, South Africa - Nakwafila, Albertina Nuusiku (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.